Restorative Justice Sebagai Alternatif Penyelesaian Kasus Pemeliharaan Landak Langka di Bali : RESTORATIVE JUSTICE SEBAGAI ALTERNATIF PENYELESAIAN KASUS PEMELIHARAAN LANDAK LANGKA DI BALI - Romadhon, Ahnaf Nur Fauzan; Fatahillah, Ikhwan Aulia (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
The concept of restorative justice is explored as an alternative approach to resolving conservation violations caused by ignorance, as demonstrated in the case of I Nyoman Sukena in Indonesia. This study aims to examine the potential for restorative justice to address such cases more humanely and effectively. A normative juridical method is applied, focusing on legal regulations and case analysis related to wildlife conservation. The findings indicate that restorative justice, emphasizing dialogue and education, can prevent recurrence and foster public awareness about protected species without imposing strict criminal sanctions. This approach, which aligns with Indonesian societal values, can reduce the judicial burden and support conservation goals.